TEMPORAL TREND IN DAILY RAINFALL INTENSITY IN A CHANGING CLIMATE IN THE MIDDLE BELT REGION OF NIGERIA - Johnson O. MAGE; Bernard T. TYUBEE (European Journal of Geography)
The study analyzed the temporal variability of daily rainfall intensity of selected stations in the Middle Belt region (MBR) of Nigeria for 46-year period (1961-2006). Daily rainfall (≥0.3mm) data were collected from eight weather stations in the study area. Daily rainfall intensity categories were classified into six categories using percentiles (P) namely; extremely light (≤ P10), light (P11 - P20 ), moderately light (P21 – P50), moderately heavy (P51 – P80), heavy (P81 – P90) and extremely heavy (> P90). To compute the percentile threshold values of the six daily rainfall intensity categories, the population of rain days was first extracted then ranked. The threshold values of the percentiles were extracted for each of the eight stations and the annual number of daily rainfall for each station were then determined. Trend in the series of the six daily rainfall intensity classes is analyzed using Mann Kendall’s test statistics (τ) and the values obtained are plotted to show the temporal variability in the region. The result shows a general increasing trend towards the light and extremely light intensity categories, though the rate of increase varies across stations and with time ranges. Light rains are increasing in the Jos plateau whereas the number of heavy events are on the decline. There is a peculiar situation in Makurdi where both extremely light and extremely heavy intensity conditions are observed to be increasing. ...